Effect of additives on the cyclic thermal stability and thermal properties of sodium acetate trihydrate as a phase change material: An experimental study. (1st January 2022) - Liu, Yunhan; Wang, Liang; Peng, Long; Zhang, Shuang; Lin, Xipeng; Han, Xiangyu; Chen, Haisheng
Highlights: Rheological behavior of composite PCMs containing different thickening agents was studied. Effect of thickening agents on cyclic stability and thermophysical properties was obtained. Optimized ratio of thickening agent and nucleating agent in composite PCMs was obtained. Abstract: As a low-cost and high-density heat storage material, sodium acetate trihydrate with sodium carboxymethyl cellulose (CMC) as a thickening agent and disodium hydrogen phosphate dodecahydrate (DSP) as a nucleating agent has the advantages of good thermal cycle stability and low supercooling degree. However, the optimal concentration and mechanism of the additives are unclear. In this study, the effects of viscosity grades of CMC and additives (CMC and DSP) of different concentrations on the cyclic thermal stability, thermal properties and phase change behavior of cPCMs were examined. The results showed that CMC with a high viscosity has a remarkable ability to maintain the thermal cycle stability of the cPCMs. However, a poor phase change behavior (decreased latent heat and increased supercooling degree) was observed with high-viscosity CMC as the thickening agent. It was also observed that excessive use of CMC or DSP results in a poor thermal stability and high supercooling degree. In addition, the viscosity of the cPCMs decayed irreversibly after several thermal cycles because of the degradation and weakened entanglement, which challenges the ability of CMC to cope with long thermal cycle environments.